(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The objective of universities is the academic success of their students, and shortcomings in this area can be manifested, from difficulties in academic performance that often leads to the student abandoning the university with the consequent social cost associated with this phenomenon, this problem being a concern of researchers in educational economics and education for several decades. This research assessed the influential factors in academic performance in Mathematics at the Faculty of Economics at the University of Havana. This was achieved from a questionnaire prepared for this study, which was validated from the analysis of Cronbach’s alpha coefficient, from which a value of 0.798 was obtained and applied to a sample that was in the first year of the degree. The instrument consists of 28 questions, some dichotomous, and others multiple choice where subjects can choose more than one alternative from a list of options. They inquire about exogenous and endogenous factors that intervene in the academic performance of students. Their identification has made it possible to measure the importance that each one acquires separately when relating them to academic performance. A proposal for actions is developed that responds to the problems identified in the analysis with the aim of contributing to raising academic performance.